ALLEGORY IN THE CHRONICLES OF NARNIA (PRINCE CASPIAN) - Virani, Humsiah (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2017)
Abstract: This study aimed to find out if the novel entitled The Chronicles of Narnia (Prince Caspian) by C. S. Lewis is the allegory base on Christian belief and the meaning of allegory found is stated on the Bible. The method used in writing this thesis is descriptive analysis method. The findings of this thesis is there are eight (8) characters taken and analyzed that had allegories and meaning of allegories out of 41 characters in the novel. From 8 characters taken and analyzed, there are 18 allegories found. 4 allegories from Caspian, 1 from Peter, 2 from Susan, 2 from Edmund, 4 from Lucy, 3 from Aslan, 1 from Trufflehunter and 1 from the Trees. The conclusion of this thesis is the all allegories found are as representation of characters and events base on Christian belief and the meaning of allegories found are stated on the Bible.